1997
DOI: 10.1056/nejm199712113372403
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Atopy with a Gain-of-Function Mutation in the α Subunit of the Interleukin-4 Receptor

Abstract: The R576 allele of interleukin-4 receptor alpha is strongly associated with atopy. This mutation may predispose persons to allergic diseases by altering the signaling function of the receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
434
2
12

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 694 publications
(465 citation statements)
references
References 41 publications
17
434
2
12
Order By: Relevance
“…Some of the IL4RA haplotypes have been shown to increase phosphorylation of binding substrates, which might result from a change in the receptor's charge and conformation, leading to tighter substrate binding. 19 However, in our study none of these combinations and indeed, no other haplotype, deviated from the expected Mendelian transmissions (see Table 6 for the five most common haplotypes).…”
Section: Resultscontrasting
confidence: 43%
See 2 more Smart Citations
“…Some of the IL4RA haplotypes have been shown to increase phosphorylation of binding substrates, which might result from a change in the receptor's charge and conformation, leading to tighter substrate binding. 19 However, in our study none of these combinations and indeed, no other haplotype, deviated from the expected Mendelian transmissions (see Table 6 for the five most common haplotypes).…”
Section: Resultscontrasting
confidence: 43%
“…Some of these polymorphisms significantly upregulate receptor response to IL-4, with a resultant increased activation of STAT6, and thus increased cell proliferation and IgE production. 17,19 Ober et al 18 have also reported an apparent haplotype effect in outbred populations. S411L (+1232 C4T) and S761P (+2281 T4C) are further single nucleotide polymorphisms (SNPs) in exon 12, but have largely been excluded from previous analyses due to low minor allele frequencies and, therefore, low statistical power.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This gene region is the location of the IL-4-receptor gene alpha, which is located at 16p11.2±12.1 (65). Initially, it was suspected that a mutation putatively leading to increased IL-4 receptor activity (Q576R) could be responsible for elevated IgE secretion (66). However, subsequent analyses have shown that polymorphisms affecting at least four different amino acids in the cytoplasmic domain of IL-4Ra may signi®cantly in¯uence the outcome of IL-4 receptor signaling and consequently IgE secretion (67).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…An international effort was made to define the markers spanning the 5q cytokine cluster by linkage analysis in a total of 11 retrospectively pooled data sets (1037 A Second-Generation Association Study of the 5q31 Cytokine Gene Cluster and the Interleukin-4 Receptor in Asthma IL4R, located on chromosome 16p12, is exceptionally polymorphic. Eight missense and six silent polymorphisms have been described [11][12][13]. Some of the polymorphisms have been reported to be associated with IgE-mediated disorders [12][13][14].…”
Section: Introductionmentioning
confidence: 99%